American Society of Hematology living guidelines on the use of anticoagulation for thromboprophylaxis in patients with COVID-19: July 2021 update on postdischarge thromboprophylaxis - Cuker, Adam; Tseng, Eric K.; Nieuwlaat, Robby; Angchaisuksiri, Pantep; Blair, Clifton; Dane, Kathryn; Davila, Jennifer; DeSancho, Maria T.; Diuguid, David; Griffin, Daniel O.; Kahn, Susan R.; Klok, Frederikus A.; et al. (Blood advances, 2022)
COVID-19–related acute illness is associated with an increased risk of venous thromboembolism (VTE). These evidence-based guidelines of the American Society of Hematology (ASH) are intended to support patients, clinicians, and other health care professionals in decisions about the use of anticoagulation for thromboprophylaxis in patients with COVID-19 who do not have confirmed or suspected VTE. ASH formed a multidisciplinary guideline panel, including 3 patient representatives, and applied strategies to minimize potential bias from conflicts of interest. The McMaster University GRADE Centre supported the guideline development process, including performing systematic evidence reviews (up to March 2021). The panel prioritized clinical questions and outcomes according to their importance for clinicians and patients. The panel used the grading of recommendations assessment, development, and evaluation (GRADE) approach to assess evidence and make recommendations, which were subject to public comment. The panel agreed on 1 additional recommendation. The panel issued a conditional recommendation against the use of outpatient anticoagulant prophylaxis in patients with COVID-19 who are discharged from the hospital and who do not have suspected or confirmed VTE or another indication for anticoagulation. This recommendation was based on very low certainty in the evidence, underscoring the need for high-quality randomized controlled trials assessing the role of postdischarge thromboprophylaxis. Other key research priorities include better evidence on assessing risk of thrombosis and bleeding outcomes in patients with COVID-19 after hospital discharge. [Display omitted]